Effectiveness of Learning Based Problem Solving with Aspect Ontology, Epistemology, Axiology to Increase Critical Thinking Ability and Understanding Thermochemical Concept of Students - Afadil, Afadil; Suyono, Suyono; Poedjiastoeti, Sri (International Journal of Active Learning, 2016)
This study is part of a development of problem solving learning model with aspects of ontology, epistemology, and axiology (Model PS-TRILOGI) to improve critical thinking skills and student understanding of Thermochemistry concepts. These objectives can be achieved if the model PS-TRILOGI is valid, practical, and effective. The study design followed the Research and Development. The effectiveness of the model PS-TRILOGI assessed by observers and implemented through the instrument test critical thinking skills and understanding of Thermochemistry concepts at 33 students in Chemistry Education Studies of Tadulako University. The results obtained showed that the percentage of positive responses given by students is very high due sense of excitement, novelty, interest, and support learning media are respectively 94.95%; 90.91%; 90.91% and 96.97%. Indicators that measure critical thinking skills is the interpretation, analysis, inference, and self-regulation. N-gain value for the indicator interpretation, analysis, and self-regulation in middle category of 0.5; while indicators inference at the high category of 0.7. Understanding of the Thermochemistry concept 13 students has a value n-gain of 0.8 to a high category. Based on the results obtained show that the model PS-TRILOGI is effective.